2009
DOI: 10.1007/s11627-008-9187-1
|View full text |Cite
|
Sign up to set email alerts
|

Alkamide production from hairy root cultures of Echinacea

Abstract: Hairy root cultures of Echinacea, one of the most important medicinal plants in the US, represent a valuable alternative to field cultivation for the production of bioactive secondary metabolites. In this study, the three most economically important species of Echinacea (Echinacea purpurea, Echinacea pallida, and Echinacea angustifolia) were readily transformed with two strains of Agrobacterium that produce the hairy root phenotype. Transformed roots of all three species exhibited consistent accelerated growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Similarly, several workers have also used the liquid medium to establish the hairy root growth (He-Ping et al 2011;Pavlov et al 2005;Romero et al 2009;Sivanesan and Ryong Jeong 2009). Few previous studies support this idea that IBA could positively affect growth and secondary metabolism of various medicinal plants (Kim et al 2003;Baque et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several workers have also used the liquid medium to establish the hairy root growth (He-Ping et al 2011;Pavlov et al 2005;Romero et al 2009;Sivanesan and Ryong Jeong 2009). Few previous studies support this idea that IBA could positively affect growth and secondary metabolism of various medicinal plants (Kim et al 2003;Baque et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently found that sugars (monosaccharide and disaccharide) induce signals that affect metabolism, development, growth, and gene expression of plants (Praveen and Murthy, 2012). The production of numerous biologically active compounds through hairy roots (such as hyoscyamine, isoflavones, sennosides A and B, pyranocoumarins, gymnemic acid, ginsenoside) was found to be affected by initial concentrations of carbon sources in the nutrient media (Liang et al, 2004;He et al, 2005;Pavlov et al, 2009;Xu et al, 2009;Romero et al, 2009;Nagella et al, 2013;Kochan et al, 2014). To date, there have been no studies regarding the effects of type and concentration of sugars on growth and accumulation of metabolites of hairy root cultures of A. montana and this motivated our study.…”
Section: Introductionmentioning
confidence: 99%
“…The neoplastic roots, produced by A. rhizogenes infection, characterized by high growth rate are demonstrated to produce higher levels of secondary metabolites or amounts comparable to that of intact plants (Romero et al 2009;Rostampour et al 2009;Shinde et al 2009). In Plumbago spp.…”
Section: Discussionmentioning
confidence: 99%
“…2001, 2002, 2003, 2004). The potential of hairy roots as a source of secondary metabolites has been recognized in several plants especially of that having root as the officinal part (Romero et al 2009;Rostampour et al 2009;Ruiz-May et al 2009;Shinde et al 2009). In these plants, large-scale production of hairy roots helps to reduce the dependence on intact plants for the drug and also to cut off the mass destruction of natural resources.…”
Section: Introductionmentioning
confidence: 99%